Environmental disclosures by the Malaysian construction sector: Exploring extent and quality - Nik Ahmad, Nik Nazli; Mohamad, Noor Afzalina (John Wiley and Sons Ltd, 2014)
We examine the extent and quality of environmental disclosures by public-listed Malaysian construction companies in their 2009 annual reports. Most of the 49 sample companies provide general disclosures which are positive and non-verifiable in nature. Very few companies disclose quantitative/non-monetary or monetary environmental information. In addition, companies did not make disclosures in eight of the items contained in the index. This suggests that environmental disclosures do not discharge the companies' accountability as disclosures are neither complete nor comprehensive enough and are largely confined to general, narrative statements which cannot be verified. To ensure accountability, regulators must introduce environmental reporting guidelines which specify content and format of the disclosures. This study addresses the paucity of Malaysian environmental disclosure literature and is one of the few which also examines quality of disclosure.